BIOSAFETY APPLIED IN MINIMALLY INVASIVE AESTHETICS - Flavia Moreira Fiorillo, Ana (Health and Society, 2023)
The aesthetics market is growing in Brazil and in the world, with promising investments in the area even with the economic slowdown. With the increase in demand for aesthetic procedures, the requirements and regulation of these activities also increase. The knowledge and application of Biosafety standards is required in these procedures in order to prevent, minimize or eliminate the risks of contamination by agents that cause infectious diseases in the life of the patient and the professional. In addition to investing in learning and technical knowledge of the procedures they perform, they must be trained in the use of protective equipment (PPE), disinfection and sterilization methods in the work environment. The objective of this article is to carry out a bibliographic review of the biosafety norms in activities aimed at minimally invasive procedures in the area of aesthetics.